Analysis of the Influence of Behavioral Factors on Accounting Performance: Case Study of Accounting Professionals at PT Company Bangun Jaya Abadi - Amin Sadiqin; Hendra Dwi Prasetyo (PT. Putra Jawa Mulya ( Putra Jawa Publisher ), 2024)
This research aims to analyze the influence of behavioral factors on accounting performance at PT. Bangun Jaya Abadi. The behavioral factors analyzed include motivation, job satisfaction, and job stress. Using a quantitative approach, this research collected data through questionnaires distributed to 100 accounting professionals at the company. The data obtained was analyzed using multiple regression techniques to identify the influence of each behavioral factor on accounting performance. The research results show that motivation and job satisfaction have a significant positive influence on accounting performance, while work stress has a significant negative impact. These findings indicate that to improve accounting performance, companies need to pay attention to and improve behavioral factors such as motivation and job satisfaction and manage work stress effectively. This research provides an important contribution to company management in designing strategies to improve accounting performance through a behavioral approach.